Urban Green Spaces and Healthy Living: A Landscape Architecture Perspective - Alessio Russo (Urban Science)
This paper examines the essential role of urban green spaces in fostering healthy living from a landscape architecture perspective. Health goes beyond the mere absence of disease to include physical, mental, and social wellbeing, all of which are greatly enhanced by accessible green spaces. By synthesising existing literature, this paper shows that urban green spaces have strong positive associations with health outcomes, especially in urban settings where environmental stressors are pronounced. The paper stresses the importance of designing attractive and accessible green spaces that encourage physical activity, mental wellbeing, and social interaction, addressing public health issues such as obesity and mental health disorders. In addition to physical and mental health benefits, the paper explores the potential of local food production through edible green infrastructure, such as community gardens, which can significantly improve diet and nutrition. Additionally, the study discusses disparities in the access to quality green spaces, particularly between the Global North and South, and advocates for equitable design strategies that serve diverse populations. Integrating evidence-based approaches into landscape architecture, the paper argues for the establishment of urban green spaces as essential elements of public health infrastructure. Finally, the paper calls for future research and policy efforts to maximise the health benefits of urban green spaces and improve the quality of life in urban environments.